1986
DOI: 10.1172/jci112303
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of regional left ventricular dysfunction after exercise-induced myocardial ischemia.

Abstract: To determine whether regional myocardial dysfunction occurring after exercise-induced ischemia might be caused by continued abnormalities of myocardial blood flow in the post-exercise period, nine dogs were instrumented with ultrasonic microcrystals for determination of circumferential segment shortening, circumflex artery electromagnetic flow probes, and hydraulic coronary artery occluders. Dogs performed treadmill exercise during partial inflation of the coronary artery occluder. When the stenosis was mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Also, exercise-or pacing-induced subendocardial ischemia has been well recognized to continue into the recovery phase as shown by persistent ST segment depression associated with continued abnormal lactate production,32,33 regional wall motion abnormalities,34 and diminished subendocardial blood flow to the affected area. 35,36 Although these electrocardiographic, metabolic, performance, and perfusion abnormalities may be less severe during early recovery than at peak pacing or exercise,32-36 they remain greater relative to heart rate during early recovery than during the development of ischemia. 32,33,36 Although the magnitude of ST segment depression during exercise can be directly related to the level of myocardial workload (as reflected by heart rate) in patients with myocardial ischemia, ST segment depression during early recovery remains greater than expected for the rapidly decreasing myocardial oxygen demand that results from an abrupt lowering of exercise load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, exercise-or pacing-induced subendocardial ischemia has been well recognized to continue into the recovery phase as shown by persistent ST segment depression associated with continued abnormal lactate production,32,33 regional wall motion abnormalities,34 and diminished subendocardial blood flow to the affected area. 35,36 Although these electrocardiographic, metabolic, performance, and perfusion abnormalities may be less severe during early recovery than at peak pacing or exercise,32-36 they remain greater relative to heart rate during early recovery than during the development of ischemia. 32,33,36 Although the magnitude of ST segment depression during exercise can be directly related to the level of myocardial workload (as reflected by heart rate) in patients with myocardial ischemia, ST segment depression during early recovery remains greater than expected for the rapidly decreasing myocardial oxygen demand that results from an abrupt lowering of exercise load.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Although these electrocardiographic, metabolic, performance, and perfusion abnormalities may be less severe during early recovery than at peak pacing or exercise,32-36 they remain greater relative to heart rate during early recovery than during the development of ischemia. 32,33,36 Although the magnitude of ST segment depression during exercise can be directly related to the level of myocardial workload (as reflected by heart rate) in patients with myocardial ischemia, ST segment depression during early recovery remains greater than expected for the rapidly decreasing myocardial oxygen demand that results from an abrupt lowering of exercise load. In effect, relative to heart rate, recovery-phase resolution of ST segment depression lags behind its exercise-phase development when coronary disease is present.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we could not exclude the possible decrease of myocardial blood flow in the endocardial layer coupled with the possible vasodilatation in the epicardial layer, even though total coronary blood flow was unchanged. Homanset al observed subendocardial ischemia 1 minute after exercise, possibly due to increased heart rate and systolic and end-diastolic pressure (9). However, left ventricular end-diastolic pressure immediately after pacing was less than 15 mmHg,indicating that the degree of ischemia was mild.…”
Section: Ischemic Preconditioningmentioning
confidence: 98%
“…This phenomenon was characterized by prolonged contractile dysfunction without a decrease in coronary blood flow after reperfusion of the coronary artery. Recently, several reports have described regional stunned myocardium induced by exercise-induced or pacinginduced ischemia (demand ischemia) in animal models (9)(10)(11)(12). Thaulowet al used an animal modelwith an ameroid constrictor on a coronary artery and found that regional myocardial stunning induced by exercise lasted for at least 30 minutes and that subendocardial blood flow 5 minutes after exercise was actually higher than the pre-ischemic value (1 1).…”
Section: Stunned Myocardium Induced By Demand Ischemiamentioning
confidence: 99%
“…Recently, such reversible contractile dysfunc tion has also been observed during recovery from exercise-induced regional ischemia in dogs with coronary stenosis (1,2). Although the mechanism responsible for this phenom enon remains unclear, several studies have reported enhancement of the recovery of the stunned myocardium with treatment of oxygen free radical scavengers, which are represented as superoxide dismutase (SOD), and have suggested that oxygen-derived free radicals, such as superoxide anion and hydroxyl radical, play an important role in mediating myocardial injury during coronary occlusion and reperfusion (3)(4)(5)(6).…”
mentioning
confidence: 90%